2015
DOI: 10.1055/s-0041-108059
|View full text |Cite
|
Sign up to set email alerts
|

Cloud-Based CT Dose Monitoring using the DICOM-Structured Report: Fully Automated Analysis in Regard to National Diagnostic Reference Levels

Abstract: Ziel: Ziel dieser Studie war die Implementierung eines Cloud-basierten CT-Dosismonitorings basierend auf dem DICOM-Structured Report (DICOM-SR) zur automatischen Überwachung der Dosisexposition im Hinblick auf die nationalen diagnostischen Referenzwerte (DRW). Material und Methoden: Zur automatischen Erfassung und Überwachung der CT-Dosisdaten wurde eine neuartige, in Kooperation mitentwickelte Software basierend auf dem DICOM-SR eingesetzt. Der DICOM-SR aller CT-Untersuchungen unserer Einrichtung zwischen 09/… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
8
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 8 publications
(10 reference statements)
1
8
0
Order By: Relevance
“…Only a few studies have used similar approaches to assess data from a large database, showing a promising and easy to use tool for audit and dose optimization purposes [20,21]. Boos et al processed and analyzed 36,523 acquisitions using a cloud-based system, showing a local radiation saving of 50%, when compared to the national diagnostic reference level, showing the same trend as in our study [22]. Another large cohort study by MacGregor et al with 36,996 examinations, showed a CTDI vol reduction of 22% over a period of 3 years [23].…”
Section: Discussionsupporting
confidence: 72%
“…Only a few studies have used similar approaches to assess data from a large database, showing a promising and easy to use tool for audit and dose optimization purposes [20,21]. Boos et al processed and analyzed 36,523 acquisitions using a cloud-based system, showing a local radiation saving of 50%, when compared to the national diagnostic reference level, showing the same trend as in our study [22]. Another large cohort study by MacGregor et al with 36,996 examinations, showed a CTDI vol reduction of 22% over a period of 3 years [23].…”
Section: Discussionsupporting
confidence: 72%
“…This goal can only be achieved if the interventionalist is capable of identifying high-dose procedures and is attentive to individual risk factors in patients [6265]. As mentioned before, a high body mass index (BMI) and previous radiation exposures are among the most important individual risk factors of patients.…”
Section: Dose Management Before During and After The Proceduresmentioning
confidence: 99%
“…Thus, high-dose procedures are uncommon in routine practice, but do occur in complex endovascular procedures. The interventionalist has, therefore, to be aware of dose monitoring tools which nowadays are an integral part of modern angiographic equipment [5, 63, 65–68]. In state-of-the-art angiographic equipment, the interventionalist gets real-time information on dose in terms of the following parameters: KERMA at reference point ( K ref ), KERMA area product (KAP) and fluoroscopy time.…”
Section: Dose Management Before During and After The Proceduresmentioning
confidence: 99%
“…Several applications have recently been developed that allows for monitoring and retrieving DICOM header information, which makes it possible to generate statistics related to a specific modality or generic features in a modality-independent way [19][20][21][22]. Moreover, radiation exposure monitoring of patients using DICOM information was also introduced [23][24][25][26] including the possibility to detect irregular radiation doses in the case of CT and digital coronary angiography (DCA) procedures. In addition, highlighted DICOM metadata elements are recommended to be monitored regularly to verify the appropriate use of SUV as an imaging biomarker when considering a successful multicenter PET/CT study [27].…”
Section: Introductionmentioning
confidence: 99%